The association between red cell distribution width and clinical outcomes in patients hospitalised due to chest pain. Issue 5 (3rd September 2019) - Topaz, Guy; Yeruchimovich, Michael; Pereg, David; Eitan, Mayan; Kitay-Cohen, Yona; Hammer, Yoav; Itzhaki Ben Zadok, Osnat; Eisen, Alon
Abstract: Background: Red blood cell distribution width (RDW) is a measure of the degree of heterogeneity of erythrocyte volume. Higher RDW levels are associated with increased mortality among patients with acute coronary syndrome (ACS), heart failure and other cardiovascular diseases. The association between RDW levels and clinical outcomes in patients admitted for further evaluation of chest pain is not known. Methods: A retrospective analysis of patients hospitalised with chest pain 2010–2016 was conducted. Patients diagnosed with ACS in the emergency department (ED) were excluded. Patients were divided into tertiles according to baseline ED RDW levels (≤13.1%, 13.1%<RDW ≤13.9%, >13.9%). Study endpoints were diagnosis of ACS during the index hospitalisation and ACS and all-cause mortality during a median follow-up of 3.3 ± 1.9 years. Results: Included were 13, 018 patients (mean age 58 ± 13 years, 61% male). Increased RDW levels were associated with higher rates of ACS in the index hospitalisation (6.1%, 6.6% and 8.1% for 1st, 2nd and 3rd tertiles, respectively, p  < .01), ACS during follow-up (8.6%, 10.1% and 13.4%, respectively, p  < .01), and with all-cause mortality during follow-up (2.5%, 4.6% and 15.4%, respectively, p  < .01). In multivariate analysis, RDW levels >13.9% (vs. ≤13.1%) were associated with ACS in the index hospitalisation (adjusted OR 1.25, 95% CI 1.04–1.51, p  = .02), ACS during follow-up (adjusted OR 1.35, 95% CI 1.05–1.73, p  = .02) and with all-cause mortality (adjusted HR 2.41, 95% CI 1.94–2.99, p  < .01). Conclusion: In this retrospective study of patients hospitalised with chest pain, higher RDW levels were associated with future ACS and long-term mortality.